2022
DOI: 10.1093/ornithapp/duac014
|View full text |Cite
|
Sign up to set email alerts
|

Age-structured model reveals prolonged immigration is key for colony establishment in Gentoo Penguins

Abstract: Understanding the mechanisms of site colonization and range expansion is crucial to understanding population dynamics, particularly for colonial seabirds that may struggle to shift their breeding ranges under climate change. We provide an alternative and simple approach to estimating the number of migrating individuals among colonies when original mark–recapture datasets are not available for use in more integrated and established methods. Here we fit an age-structured population model with published vital rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…This is true even of the Southern cluster colonies, which are known to be recently established, and yet had only a moderate increase in ROH and short between‐colony IBD segments consistent with only a minor decrease in effective population size. Herman and Lynch (2022) found that continued – and in some cases increasing – immigration is essential for observed population growth in recently colonized gentoo penguin colonies, which is supported by our findings. This may help to buffer nascent colonies from Allee effects, as colonial seabird fledglings are vulnerable to predation and larger cohorts reduce the probability of being depredated (Schippers et al., 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is true even of the Southern cluster colonies, which are known to be recently established, and yet had only a moderate increase in ROH and short between‐colony IBD segments consistent with only a minor decrease in effective population size. Herman and Lynch (2022) found that continued – and in some cases increasing – immigration is essential for observed population growth in recently colonized gentoo penguin colonies, which is supported by our findings. This may help to buffer nascent colonies from Allee effects, as colonial seabird fledglings are vulnerable to predation and larger cohorts reduce the probability of being depredated (Schippers et al., 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Eight new colonies of gentoo penguins have been established on the WAP in the last 30 years concurrent with local sea ice decline (Herman et al., 2020). Continued immigration of individuals has been shown to sustain population growth at least during the early colonization phase of such colonies (Herman & Lynch, 2022). This movement of individuals was estimated to account for approximately 7.6% of the entire gentoo penguin population on the WAP, a scale of ongoing range expansion that is to our knowledge unprecedented in this region.…”
Section: Introductionmentioning
confidence: 99%
“…The compensation of both declining immigration and increasing inbreeding by breeder survival, resulting in a significantly greater number of established breeders over time (Table S2), demonstrates that significant shifts in local demography were required to maintain population stability through increasing isolation. Multiple studies have documented how increasing immigration drove increases in other vital rates that allowed newly-established populations to become self-sufficient source populations (Herman & Lynch 2022; Santoro et al . 2016; Tenan et al .…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have documented growing or stable gentoo populations at established colonies in this region (e.g., Brown Bluff, D’Urville Monument 7 ), our expedition found a small gentoo colony at Cape Scrymgeour that appears to be a new colonization and, with the exception of a single nest reported from nearby Jade Point, the most southerly colony of this species on the Weddell Sea side of the Peninsula. Based on patterns of growth of new gentoo colonies 50 , we estimate that the Cape Scrymgeour population has been in existence at least 5 years and possibly longer absent continued immigration from other established populations. While gentoo penguin population expansions along their southern range margin on the western side have been well reported 29 , our findings provide further evidence of gentoo range expansion along the southern margins of their range east of the Antarctic Peninsula in the northern Weddell Sea.…”
Section: Discussionmentioning
confidence: 99%